COVID-19 pneumonia and the administration of antibiotics if needed - Abdulfatah Saed (African Journal of Advanced Pure and Applied Sciences, 2022)
Everyone has developed a habit of discussing COVID-19. The COVID-19 epidemic has made respiratory sickness, including infection, pneumonia, and mortality, front-page news. Many of us have been waiting for and fearing the next global respiratory pandemic. 2019 marks a century since the end of the 1918 H1N1 influenza A pandemic, and many were amazed that we had gone so long without a comparable recurrence. Even though there have since been other global pandemics, the 1918 influenza pandemic stood out because it lasted for more than a year, affected approximately one-third of humanity, and claimed the lives of more than 50 million people.